AN EMPIRICAL ANALYSIS OF THE IMPACT OF SUBWAY ON HOUSING PRICE-TAKE HANGZHOU AS AN EXAMPLE - Gong, Zhuo (International Journal For Research In Business, Management And Accounting, 2018)
Housing price in medium and large cities in China has been rising for a long time and still remains at a high level. This paper studies the phenomenon and takes Hangzhou No.1 Subway as an example. By using Hedonic model, this paper analyzes factors affecting the housing price such as age of house, traffic, area, etc. Through empirical analysis, we draw conclusion that among these factors, transportation is the most important factor affecting the housing price. Therefore, the improvement of traffic such as subway can ease the housing pressure within urban areas and can also improve the housing price outside the urban effectively.